The Effect of PGF2α Injection on Post-Thaw Motility in Sperm of Nubian Goats - Aswadi Aswadi; Husnurrizal Husnurrizal; Mulyadi Adam; Tongku Nizwan Siregar (Buletin Peternakan, 2021)
This study aims to determine the effect of PGF2α injection on the post-thaw motility (PTM) in sperm of Nubian goats. Three male Nubian goats (3-4 years) with good reproductive ability were used. This study used a 3 x 3 Latin square design. The experimental animals received a physiological NaCl injection as a control (P1); 37.5 mg of PGF2α (P2), and 75 mg of PGF2α (P3). Semen was collected using an artificial vagina with one-week storage intervals between treatments. The collected semen was then diluted and frozen using a simple freezing method. Observation of semen quality before freezing included macroscopic and microscopic examinations. Macroscopic examination consisted of volume, pH, color, odor, and consistency, while microscopic examination consisted of motility, concentration, viability, and abnormality. PTM examination was done by mixing a drop of sperm suspension and one drop of physiological NaCl on an object glass and covered prior to observation under microscope.. The results were analyzed using a Latin square pattern variant analysis, followed by Duncan's test. The PTM values of sperm (%) of Nubian goats in P1, P2, and P3 respectively are 28.71±10.24, 50.03±13.70, and 54.84±12.04 (P<0.05). Injection of PGF2α to Nubian goats by injection increased the PTM.